(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2008)
HLA genetic matching of donor and recipient is an important requirement for optimizing outcome following hematopoietic stem cell transplantation (HSCT). However, other non-HLA genes are being investigated for their role in graft-versus-host disease incidence and severity and in survival, by modulating the intensity of inflammation and tissue injury. These non-HLA-encoded genes include cytokine genes with polymorphisms within the 5' or 3' regulatory sequences of the genes. The polymorphisms or microsatellites may alter the transcription factor binding sites within the gene promoters and the amount of cytokine produced. This chapter summarizes the potential role of these genetic polymorphisms regarding the cytokines in predicting outcome of HSCT.